2019
DOI: 10.3389/fmicb.2019.02316
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Ethanol Productivity of Zymomonas mobilis 8b in Enzymatic Hydrolysate of Dilute Acid and Ammonia Pretreated Corn Stover Through Medium Optimization, High Cell Density Fermentation and Cell Recycling

Abstract: The presence of toxic degradation products in lignocellulosic hydrolysate typically reduced fermentation rates and xylose consumption rate, resulting in a decreased ethanol productivity. In the present study, Zymomonas mobilis 8b was investigated for high cell density fermentation with cell recycling to improve the ethanol productivity in lignocellulosic hydrolysate. The fermentation performances of Z. mobilis 8b at various conditions were first studied in yeast extract-tryptone medium. It was found that nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Compared with the fermentation under 50 g/L xylose and 100 g/L xylose, the xylose consumption and ethanol production were decreased in all three strains under 150 g/L xylose. This phenomenon was consistent with previous works that the higher the xylose concentration is, the more difficult it is for cells to complete fermentation [ 12 , 16 , 39 ]. It can be attributed to the production of ethanol and toxic intermediates derived from xylose such as xylitol and xylonate [ 31 , 40 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the fermentation under 50 g/L xylose and 100 g/L xylose, the xylose consumption and ethanol production were decreased in all three strains under 150 g/L xylose. This phenomenon was consistent with previous works that the higher the xylose concentration is, the more difficult it is for cells to complete fermentation [ 12 , 16 , 39 ]. It can be attributed to the production of ethanol and toxic intermediates derived from xylose such as xylitol and xylonate [ 31 , 40 ].…”
Section: Resultssupporting
confidence: 93%
“…The result suggested that sugar sources had a great effect on cell growth, and glucose was superior to xylose as the carbon source for ethanol fermentation. The slower consumption of xylose and less energy generation for cell growth may be the main reason for slower xylose metabolism as reported before [ 39 ]. As depicted, all strains could consume 50 g/L glucose completely to get a maximum OD 600 around 5.20 and ethanol titer around 25 g/L (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…57 For example, a self-flocculating H. campaniensis LS21 strain has been successfully constructed for wastewater- less PHB fermentation, 58 and a previous study also demonstrated that high cell density fermentation with cell recycling in Z. mobilis 8b can improve the ethanol titer and metabolic yield in a lignocellulosic hydrolysate. 59 Therefore, it is feasible to deploy the cell recycling in the recombinant PHB-producing Z. mobilis strain to produce PHB and ethanol simultaneously.…”
Section: Continuous Co-production Of Ethanol and Phbmentioning
confidence: 99%
“…Zymomonas mobilis is an ethanol-tolerant bacterium that ferments a wide variety of monosaccharides and produces bioethanol in significant quantities ( Kurumbang et al, 2019 ). It possesses some unique properties that make it an excellent candidate to be considered as a substitute for yeast in the manufacturing of bioethanol ( Li et al, 2019 ). Utilizing this bacterium as an expression platform for recombinant protein shows about 12–30 times higher protein expression when compared to E. coli ( Kurumbang et al, 2019 ).…”
Section: Expression Of Thermostable Cellulase and Xylanasementioning
confidence: 99%